SKILLS OF A SPORTS MANAGER IN WORK WITH PEOPLE - Radovan Čokorilo; Zoran Milošević; Milana Grk (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Work with people represents a highly significant field of sports manager,s activities in which his professional knowledge, leadership and personal traits and skills are manifested. This is due to the fact that inertial plans and organisational schemes are filled by people who are to be transferred to on active (living) process of activities, while potential energy and talents should be converted from the resources to the results. Even the best management plan fails to be implemented unless a sports manager ressesses a skill to establish and channel complex human relations towards goals of on organisation. It is just the implementation of the management function. through which a sports manager shows his/her true value. This value rests on selfunderstanding, understanding people involved in cooperation, understanding different situations in which he/she acts, development of tolerance and flexibility in human relationship etc. The purpose of this paper is to design a desirable profile of a personality which might serve either as a paradigm of sports managers, development or an assumption of raching functional obility for this profession on the basis of a practical manager,sexperience and theoretical psychological knowledge.